Stories of wonders and wishes - Blyton, Enid (2022)
Prepare to be dazzled with stories of witches, wizards and magical folk. From spells and enchantments to potions and wishes, there's magic and wonder brewing in this bumper collection by Enid Blyton.
The wish that came true -- The magic bicycle -- The astonishing curtains -- The grand birthday cake -- The flopperty bird -- The wonderful garden -- The house in the fog -- The magic brush -- The very strange pool -- The silly little conker -- The boy whose toys came alive! -- A pennyworth of kindness -- The astonishing ladder -- The impossible wish -- The house made of cards -- The salt, salt sea -- The goblin in the train -- The box of magic -- The unlucky little boy -- The little silver hat -- The toys' new palace -- Blackberry magic -- Foolish Caryll -- The treasure hunt -- The little old toymaker -- Sally Suck-A-Thumb -- A wonderful thing -- His little sister -- In the King's shoes -- The ship in the bottle -- The two good fairies -- The wonderful conjurer.
Keywords: Children's stories, English; Children's stories, English; Children's stories; Short stories; Fantasy fiction